2017
DOI: 10.1007/s00401-017-1707-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of tau protein in health and disease

Abstract: Tau is well established as a microtubule-associated protein in neurons. However, under pathological conditions, aberrant assembly of tau into insoluble aggregates is accompanied by synaptic dysfunction and neural cell death in a range of neurodegenerative disorders, collectively referred to as tauopathies. Recent advances in our understanding of the multiple functions and different locations of tau inside and outside neurons have revealed novel insights into its importance in a diverse range of molecular pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
730
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(789 citation statements)
references
References 547 publications
6
730
4
4
Order By: Relevance
“…Tauopathies are pathologically and phenotypically diverse, and include Alzheimer's disease (AD), progressive supranuclear palsy, corticobasal degeneration, chronic traumatic encephalopathy, Pick's disease, and frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17) (1)(2)(3)(4). Tau is abundant in neurons and expressed at lower levels in glia (1,6,7), and primarily stabilizes microtubules (MTs) among other diverse physiological functions (1,5,8,9). Six different isoforms of tau, ranging from 352 to 441 amino acids, are expressed in the adult human brain as a result of alternative splicing (10,11).…”
mentioning
confidence: 99%
“…Tauopathies are pathologically and phenotypically diverse, and include Alzheimer's disease (AD), progressive supranuclear palsy, corticobasal degeneration, chronic traumatic encephalopathy, Pick's disease, and frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17) (1)(2)(3)(4). Tau is abundant in neurons and expressed at lower levels in glia (1,6,7), and primarily stabilizes microtubules (MTs) among other diverse physiological functions (1,5,8,9). Six different isoforms of tau, ranging from 352 to 441 amino acids, are expressed in the adult human brain as a result of alternative splicing (10,11).…”
mentioning
confidence: 99%
“…Protein interactions involving the microtubule-binding repeats or the poly-proline region of tau have been reported before (17,18). However, N-terminal tau interactions and its sequence-dependent requirements remain poorly understood.…”
Section: Differential Interaction Mediated By Aa 18-28 Of Human Taumentioning
confidence: 95%
“…Mutations in MAPT do not cause AD, however there are several lines of evidence strongly supportive of a crucial role for tau in the AD pathological cascade. A comprehensive review of the role of tau protein in health and disease can be found here (16). Further, experimental models have demonstrated that tau reduction is neuroprotective against amyloid, demonstrating an essential role for tau as a mediator of amyloid toxicity (23,43).…”
Section: The Importance Of Tau In Neurodegenerationmentioning
confidence: 99%